Trillion dollar estimate: Illicit financial flows from developing countries - Volker Nitsch (Technische Universität Darmstadt, Department of Law and Economics, 2016)
Recent estimates suggest that developing countries lose about 1 trillion US dollars each year due to illicit financial flows. This paper reviews the empirical methodology that underlies those estimates. Various critical aspects of the analytical approach are highlighted, focusing in particular on deficiencies in the use of mirror trade statistics to quantify the extent of capital outflows due to trade misinvoicing. Serious issues in the empirical analysis include, among others, arbitrary assumptions, mixed methodologies and skewed sampling. As a result, it is argued that the quantitative results obtained from those exercises have no substantive meaning. The trillion-dollar estimate of illicit financial flows from developing countries, therefore, lacks evidence and is uncorroborated.
urn:nbn:de:tuda-tuprints-54379
Keywords: F14; F38; 330; trade misinvoicing; mispricing; capital flight